Analysis of Product Quality Control of Visors Using the Seven Quality Tools Method at PT. Solo Plastik Indonesia - LIA MILANA; Dimas (Universitas Majalengka, 2026)
Quality control is a critical aspect of the production process to minimize non-conforming products (NG). PT. Solo Plastik Indonesia still encounters quality issues in visor products, particularly silver and jetting NG. This internship research aims to analyze visor product quality control using the Seven Quality Tools method with a descriptive quantitative approach. Data were collected through direct observation, production and NG records, and interviews with visor production operators. The analytical tools applied include checksheets, histograms, stratification, Pareto diagrams, P control charts, scatter diagrams, and cause-and effect (fishbone) diagrams strengthened by observational indicators and quantitative scoring. Pareto analysis results show that in shift 1, silver and jetting NG are the dominant NG types with a cumulative percentage of 84%, while in shift 2 the cumulative percentage reaches 81%. P control chart analysis indicates that each shift has three out-of-control points, indicating that the production process is not yet fully under statistical control. Fishbone analysis shows that the material factor has the highest score contribution at 31,25%, followed by method at 30% and machine at 22,5%, while environment and man factors contribute 8,75% and 7,5%, respectively, and the measurement factor contributes 0%. Overall, the application of Seven Quality Tools is effective in identifying dominant NG types and their main causes as a basis for quality improvement at PT. Solo Plastik Indonesia.